A Long-Standing Case of Venous Leg Ulcer Treated with Constitutional Homoeopathic Medicine: A Case Report - Yadav, Ajay Kumar; Rath, Prasanta; Das, Kapil; Tiwari, Anil Kumar; Sharma, Monika (Homœopathic Links, 2023)
Venous leg ulcers, also called varicose or stasis ulcers, are a result of damage to the valves in the veins of the legs, which increases venous pressure. Chronic venous insufficiency (CVI) is a well-known factor that contributes to the emergence of venous leg ulcer. Blood reflux, obstruction, or a combination of both mechanisms may result in CVI and lead to macro- and microcirculatory dysfunction. The primary risk factors for venous ulcer development are older age, obesity, previous leg injuries, deep venous thrombosis and phlebitis.A 57-year-old patient, with a pre-diagnosed case of venous leg ulcer, presented to the outpatient department of National Institute of Homoeopathy, Kolkata, with complaints of swelling and multiple ulcers in both legs. The ulcers were shallow and irregular in shape and presented with itching and persistent sticky discharge. The leg ulcer completely healed within two and half months of duration with Graphites 30/4 doses, which were given as a constitutional homoeopathic medicine. The outcome assessment of this case was done by using the Modified Naranjo Criteria (MONARCH) inventory. This case study suggests homoeopathic treatment as a promising complementary or alternative therapy, emphasising the significance of repertorisation in constitutional homoeopathic prescription for the management of ulcers.
Keywords: chronic venous insufficiency; venous leg ulcer; homoeopathy; MONARCH; case report